2010
DOI: 10.1002/term.287
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered constructs based on SPCL scaffolds cultured with goat marrow cells: functionality in femoral defects

Abstract: This study aims to assess the in vivo performance of cell-scaffold constructs composed of goat marrow stromal cells (GBMCs) and SPCL (a blend of starch with polycaprolactone) fibre mesh scaffolds at different stages of development, using an autologous model. GBMCs from iliac crests were seeded onto SPCL scaffolds and in vitro cultured for 1 and 7 days in osteogenic medium. After 1 and 7 days, the constructs were characterized for proliferation and initial osteoblastic expression by alkaline phosphatase (ALP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
(33 reference statements)
2
38
0
Order By: Relevance
“…In higher strain environments, cellular differentiation favors osteoclasis and chondrogenesis or fibrogenisis. 18 This was not visualized in other study group animals (control six weeks and static six weeks), which can probably be explained by the short time of the weight-bearing of the limb, since during the first two weeks a limb immobilization by a modified RobertJones bandage was applied in the operated limb (of the all animals). However, the stress was not observed in the groups static 12 weeks and bioreactor 12 weeks, due to the mechanical support provided by the SPCL constructs, that supported the load together with the bone fixation device(plate and screw), since the device was loaded with the purpose of compressing the stacked GBMSCs-SPCL constructs.…”
Section: Discussionmentioning
confidence: 82%
“…In higher strain environments, cellular differentiation favors osteoclasis and chondrogenesis or fibrogenisis. 18 This was not visualized in other study group animals (control six weeks and static six weeks), which can probably be explained by the short time of the weight-bearing of the limb, since during the first two weeks a limb immobilization by a modified RobertJones bandage was applied in the operated limb (of the all animals). However, the stress was not observed in the groups static 12 weeks and bioreactor 12 weeks, due to the mechanical support provided by the SPCL constructs, that supported the load together with the bone fixation device(plate and screw), since the device was loaded with the purpose of compressing the stacked GBMSCs-SPCL constructs.…”
Section: Discussionmentioning
confidence: 82%
“…The orthotopic location in vivo is expected to provide more accurate outcomes concerning the influence or local effects of implanted cells or cell scaffold constructs where they were initially designed to be functional [40]. The ulna defect is appropriate for in vivo tests as it does not require further internal or external fixation, which might influence the outcome of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the defects were not completely bridged, new bone was present in the center of the defect, with large areas of matrix and connective tissue formation, confirmed by Masson’s Trichrome staining and representative micro-CT scanning, particularly in SPCL + ASCs explants. Most of the similar studies reported in literature, use stem cells that are pre-differentiated into the osteogenic lineage prior to implantation 22,5053 . This study demonstrates that non-differentiated ASCs enhance the process of bone regeneration when used in tissue engineering strategies.…”
Section: Discussionmentioning
confidence: 99%